Dynamics of Domestic Labour across Short- and Long-Distance Family Relocations - Vidal, Sergi; Baxter, Janeen; Perales, Francisco; Perales, F; Vidal, S (My University, 2016)
Family relocations within developed countries are argued to have gendered consequences for paid employment, with men's careers improving and women's careers deteriorating. However, little is known about their potential relationships with outcomes in other life domains, including partnered men's and women's relative shares of domestic labor. The authors addressed this gap in knowledge by theorizing and examining how within-couple gender gaps in domestic work evolve across short- and long-distance family relocations over the life course, paying attention to the over-time dynamics before and after event occurrence. To accomplish this, they used 12 years of panel data from the Household, Income and Labour Dynamics in Australia Survey and panel regression models. The results indicated that family relocations widen the within-couple gender gap in weekly housework hours, largely because of shifts in women's employment situation and fertility episodes that accompany residential relocations.
Keywords: Employment; Gender; Labour market; Gender; Employment; Gender; Gender; Employment and unemployment